The moderating effect of perceived organizational support: The impact of psychological capital and bidirectional work-family nexuses on psychological wellbeing in tourism - Bai, Na; Yan, Zhen; Othman, Rosly (Frontiers in Psychology, 2023)
The novel coronavirus (COVID-19) has inflicted unprecedented damage on the tourism industry. However, the psychological health fallout of COVID-19 on tour guides has not received empirical attention yet. Therefore, the present study aims to examine how psychological capital (PsyCap) improve tour guides’ psychological well-being (PWB), the mediating effect of work–family conflict (WFC), family–work conflict (FWC), work–family facilitation (WFF) and family–work facilitation (FWF), and the moderating effect of perceived organizational support (POS). For this quantitative research, the data were collected from 276 tour guides in China. The results indicate that PsyCap significantly mitigates two directions of work-family conflict and intensifies two directions of work-family facilitation in order to promote tour guides’ PWB. Furthermore, POS moderates the direct effect of two directions of conflict and facilitation on PWB and also moderates the indirect effect of PsyCap on the aforesaid outcome via two directions of conflict and facilitation. Theoretical and practical implications, limitations and future research directions are provided.